CHEMICAL CONSTITUENTS OF LIGULARIA NARYNENSIS - Jenis Janar; Yang Ye.; Nurlybekova Aliya K. (Academic Scientific Journal of Chemistry, 2019)
In this work, the quantitative and qualitative analysis of phytochemical constituents of medicinal plant Ligularia narynensis from Kazakhstan have been made for the first time. Total bioactive components of L. narynensis such as organic acids (0.58 %), flavonoids (0.64 %) and together with moisture content (5.98 %), total ash (7.58 %), and extractives content (25.1 %) were determined. Eleven macro-, microelements from the ash of plant were identified, main contents of them were K (1308.25 µg/ml), Ca (1312.77 µg/ml), and Mg (231.18 µg/ml) by using method of multi-element atomic emission spectral analysis. In addition, the ethyl acetate extract from the aerial part of L. narynensis was analyzed by Liquid Chromatography-Mass Spectrometry (LC-MS).